An open label pilot study of micro expression recognition training as an intervention for low mood - Kasia Wezowski; Ian S. Penton-Voak (Scientific Reports)
Abstract The present study is a pilot, open-label study which assessed whether training using the Micro Expression Training Tool for 3 weeks is effective in improving micro expression processing, mood, and social functioning. Participants completed four training sessions and could practice additionally, if they wished to. Measures of low mood and social functioning were made prior to and after the training in order to assess potential therapeutic effects. The results showed strong evidence for an effect of training on improvement in micro expression recognition, reflected in higher scores after training, and an association between the number of sessions done and the degree of improvement. In an adjusted model, there was an improvement in low mood, which should be investigated in future studies. There was no effect of micro expression recognition training on social functioning. This pilot study demonstrates a new, effective method for training micro expression processing and shows that it has potential for mood improvement, which may be beneficial for the halting of sub-clinical depression.